The Development of State and National Symbols in Central Europe Common Historical Experiences and Unique Characteristics in the History of Symbols of Five Countries - Tóth Zoltán J. (INTERNATIONAL AND COMPARATIVE LAW REVIEW, 2023)
State symbols can be considered an important element of the existence of every independent state. State symbols perform important functions both internally and externally (in relation to other countries and international communities). State symbols developed and changed along with the development of the given state and society. The article deals with the development of state symbols in five Central European countries, namely the Czech Republic, Slovakia, Poland, Hungary and Slovenia. The authors analyze the individual state symbols of these states, their development and meaning, at the same time pointing out differences, but also similarities within these European states and their often common history.